1994
DOI: 10.1073/pnas.91.16.7727
|View full text |Cite
|
Sign up to set email alerts
|

A mutant epidermal growth factor receptor common in human glioma confers enhanced tumorigenicity.

Abstract: The development and neoplastic progression of human astrocytic tumors appears to result through an accumulation of genetic alterations occurring in a relatively defined order. One such alteration is amplification of the epidermal growth factor receptor (EGFR) gene. This episomal amplification occurs in 40-50% of glioblastomas, which also normally express endogenous receptors. Moreover, a significant fraction of amplified genes are rearranged to speifically eliminate a DNA fragment containing exons 2-7 of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
697
2
10

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 838 publications
(743 citation statements)
references
References 39 publications
34
697
2
10
Order By: Relevance
“…In all cases the cell lines exhibiting the EGFRvIII had an increased growth potential or ability to form tumors in the nude mouse model. 22,25,27,30,44 The in vitro invasion assay can mimic some of the events leading to the formation of metastasis, that is, attachment to the basement membrane, local proteolysis and migration. Various growth factors have been implied to play a significant role in the processes leading up to the formation of metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases the cell lines exhibiting the EGFRvIII had an increased growth potential or ability to form tumors in the nude mouse model. 22,25,27,30,44 The in vitro invasion assay can mimic some of the events leading to the formation of metastasis, that is, attachment to the basement membrane, local proteolysis and migration. Various growth factors have been implied to play a significant role in the processes leading up to the formation of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has demonstrated that the EGFRvIII could be detected at the cell surface. 30 In the present study, we report our results from the expression of EGFRvIII in an EGFR-negative small cell lung cancer (SCLC) cell line. We used the Tet-On expression system and evaluated the expression of EGFRvIII in the absence and presence of doxycycline.…”
mentioning
confidence: 97%
“…Results were also separately con®rmed using scanning densitometry. In U87MG cells, the EGFr is overexpressed and appears to mediate the transformed phenotype (Libermann et al, 1985;Nishikawa et al, 1994). In U87/T691 cells, the T691stop mutant proteins heterodimerize with the EGF receptor, suppressing transformation characteristics of these tumor cells (O'Rourke et al, 1997).…”
Section: Subcellular Localization Of the P215 Brca1 Polypeptidementioning
confidence: 99%
“…The ectopic expression of the EGFRvIII in a glioblastoma cell line increased the speed with which these cells formed tumors in nude mice (Nishikawa et al, 1994;Nagane et al, 1996). The EGFRvIII is also capable of significantly enhancing the tumorgenicity of immortalized murine fibroblasts Moscatello et al, 1996) and the breast cancer cell line MCF-7 (Tang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Using the murine hematopoietic 32D cell line, Tang et al (2000) demonstrated that the EGFRvIII is capable of directly transforming a non-tumorigenic cell line. Unlike the wild-type (WT) EGFR, the EGFRvIII is unable to bind to EGF or transforming growth factor-α (Ekstrand et al, 1994;Nishikawa et al, 1994;Moscatello et al, 1996) but, instead, it can dimerize spontaneously (Moscatello et al, 1996;Fernandes et al, 2001;Montgomery, 2002). The spontaneous dimerization and ensuing TK activation of the EGFRvIII is necessary to transform cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;O'Rourke et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%